Educação e tecnologia: as TICs como instrumento pedagógico em um Centro Educacional Infantil de Parintins, Amazonas - Souza, Hugo Victor Castro de (BRASIL, 2024)
This work had the premise of analyzing the use of information and communication technologies as a pedagogical tool in a Children's Educational Center, located in the Rural Zone of the Municipality of Parintins, presenting as its main objective to analyze how digital technologies have been used and identify and understand what they are their main difficulties in relation to the use of technologies. The subjects of our field research were around 6 teachers, all from Early Childhood Education at a Children's Educational Center in the Rural Zone of the Municipality of Parintins/AM, in addition to 118 students at the same level of education, from 6 different classes, being Kindergarten, 1st Period and 2nd Period, morning and afternoon. It should be noted that the research was carried out during the beginning of the academic year at that Center. As methodological procedures, it was decided to use a qualitative approach, adopting direct observation among students in the classes involved in the research as data collection techniques, as well as the application of two open questionnaires, consisting of 08 questions to the Center Manager and 03 questions directed to teachers. To achieve the proposed objectives, we carried out a bibliographic study based on the theoretical assumptions of some scholars, such as Kenski (2007), Santos et al. (2020 and 2021); BNCC (2017), among others. In short, the research showed that there is still great difficulty in implementing ICTs within the classroom, either due to a lack of infrastructure or a lack of specialized courses for education agents.